Immunotoxicity, genotoxicity and epigenetic toxicity of nanomaterials: New strategies for toxicity testing?. (November 2017) - Dusinska, Maria; Tulinska, Jana; El Yamani, Naouale; Kuricova, Miroslava; Liskova, Aurelia; Rollerova, Eva; Rundén-Pran, Elise; Smolkova, Bozena
Abstract: The unique properties of nanomaterials (NMs) are beneficial in numerous industrial and medical applications. However, they could also induce unintended effects. Thus, a proper strategy for toxicity testing is essential in human hazard and risk assessment. Toxicity can be tested in vivo and in vitro ; in compliance with the 3Rs, alternative strategies for in vitro testing should be further developed for NMs. Robust, standardized methods are of great importance in nanotoxicology, with comprehensive material characterization and uptake as an integral part of the testing strategy. Oxidative stress has been shown to be an underlying mechanism of possible toxicity of NMs, causing both immunotoxicity and genotoxicity. For testing NMs in vitro, a battery of tests should be performed on cells of human origin, either cell lines or primary cells, in conditions as close as possible to an in vivo situation. Novel toxicity pathways, particularly epigenetic modification, should be assessed along with conventional toxicity testing methods. However, to initiate epigenetic toxicity screens for NM exposure, there is a need to better understand their adverse effects on the epigenome, to identify robust and reproducible causal links between exposure, epigenetic changes and adverse phenotypic endpoints, and to develop improved assays to monitor epigenetic toxicity. Highlights: NMs can induce immunotoxic effects, causing death of immune cells or by affecting immune-specific signaling pathways. Genotoxic action can be either direct (damaging DNA) or indirect (via oxidative stress, resulting in DNA base oxidation). Current strategies address immunotoxicity and genotoxicity (DNA damage, gene mutations, chromosomal damage and aneuploidy). For complete characterization, epigenetic endpoints should be included to battery of conventional toxicity testing methods. Better understanding of functional relationships between NM exposure, epigenetic deregulation and phenotype is required.